Treasures of Fairy Tale Texts at The Pakualaman Scriptorium - Rahmat Rahmat; Sangidu Sangidu; Sri Ratna Saktimulya (Javanologi: International Journal of Javanese Studies, 2024)
Pakualaman scriptorium is one of the places where manuscripts are created in Java. From this place, works in a number of genres were created. One of the genres is fairy tales. However, there is no exact information on the number of fairy tale texts and their story content. Therefore, this research is expected to be a bridge to overcome this problem. The theory used is philology with manuscript data sources and text data. Data were collected through observation by checking all manuscripts and the entire text and analyzed descriptively. Data presentation is in the form of the number of manuscripts, the number of fairy tale texts, and the main content of the story. The research show that there are thirteen manuscripts containing fairy tale texts. The number of texts is thirty-seven, namely Adigang, Adigung, Adiguna, Ajidipa, Bayan Budiman, Bĕton Papat Gosong Kabèh, Cantrik lan Manuk Prĕnjak, Dhalang Jagur, Dhayoh Sarwa Nyilih, Jaka Kusnun, Jaka Sabar, Jodholan,  Kancil (a and b version), Katiban Woh Lo, Kĕmit Papat lan Raja Prayitna, Ki Jaka, Ki Jajĕrih, Ki Maradiwangsa, Ki Maratruna, Kyai Prĕlambang, Laré Mĕnjété, Lĕmut lan Gajah Dhĕlikan, Ngabèhi Ngĕbulpus, Pak Bĕja, Pambĕngé Landhak, Panji Brangtairawan, Patih Brihaban, Prabangkara, Pukitranganingtyas, Radèn Mukjijat, Istijrat, lan Kĕramat, Raja Nĕdya Khaji, Raja Ngadil Suryaning Alam, Raja Wisana, Randha Kasiyan, Tikus lan Gajah Totohan, Watak Dhasar Kucing, Wĕsi Pinangan Rayap, Wong Ngĕmis Lĕnga, Wong Wayuh. The texts contain good or bad moral values. Based on distribution map, the Pakualaman scriptorium fairy tale texts are stored in Pakualaman, Yogyakarta Palace, Sanabudaya Museum, and Leiden University.